mu TESLA Protocol in Vehicular Networks - Conceicao, Rodrigo Martins da [UNESP]; Lobato, Renata Spolon [UNESP]; Manacero, Aleardo [UNESP]; Spolon, Roberta [UNESP]; Cavenaghi, Marcos Antonio; IEEE (Ieee, 2017)
It is estimated that in the near future vehicles will be equipped with electronic devices allowing communication among vehicles. This communication should enable the exchange of traffic data, such as accidents, traffic jams or the approaching of emergency vehicles. This exchange, however, cannot be done through simple messages. It is necessary to perform it as safe and efficient as possible, avoiding common network security problems. This paper proposes the use of mu TESLA protocol to implement message authentication broadcasting in vehicular networks, which should enhance the safety in the information exchange. The proposal is validated through feasibility and performance analysis, which results are included at the end of the paper.
Keywords: VANETs; mu Tesla; authenticaion; security